سودی نظام کا خاتمہ (سیرت النبی ﷺ کی روشنی میں ): Demolishing of the interest based economical system in the light of Seerat un Nabi - Ata Ullah; Abdul Qayyum (MEI, 2023)
The reformation of the muslim socity lies only in acting upon the Holy prophet (Peace be upon Him) came to purge the Society from moral diseas. He not only for forbade people committing against crimes immoral deeds but also ordered His followers to abstain from the curse of usury (interest on loan ) Usuary is such a curse where all the wealth is accumulated in few hands, and the weak and oppressed class of the Society become indebted to them to fulfill their needs. Even the Arab tribes used to practice transaction based on usury.But when Islam came, Holy Prophet forbade them from this and command them to avoid this ignorant practice and dissolved the interest of Hazrat Abbas. Islam prohibited usury gradually so that immoral practices could be eliminated from the muslim society and the Muslims could lead peaceful and serene lives.